MADRASAH DAN TRANSFORMASI INTELEKTUAL - muhdi Muhdi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2015)
This paper attempts to map the characteristics of the development of theclassical era of Islamic schools (madrasah). The study concludes that thesedevelopments have significant relevance for the future direction of theIslamic intellectual transformation until today. The Character of schooldevelopment in classical era which gave full attention to the transfer ofconventional religious sciences gave its own color for the implementation ofreligious life as well. Islamic Jurisprudence (Fiqh) which provided practicalconcepts in religious life became a definite curriculum content. This is aremarkable achievement. However, lately, the trend is considered to makethe development of Islamic intellectual transformation become "unhealthy".This unhealthiness is the stressing point of this paper.